PEMBERDAYAAN KELOMPOK KADER MELALUI PROGRAM DAPUR GIZI SEBAGAI UPAYA PENCEGAHAN STUNTING DI POSYANDU DAHLIA DESA KABASIRAN - Andi Muh Asrul Irawan; Andi Mukramin Yusuf; Ema Komalasari; Alfina Ananda; Naila Maritza Putri; Khanza Aulia (Jurnal Abdi Insani, 2026)
Stunting is a condition of growth failure in children due to chronic malnutrition that has become a primary concern at Posyandu Dahlia. This is concerning considering Bogor Regency ranks as the second highest for stunting in West Java with a prevalence of 27.6%. The purpose of this community service program is to address three priority issues at Posyandu Dahlia: the lack of knowledge among cadres about stunting, limited kitchen facilities, and insufficient variety of supplementary food for toddlers. The implementation method was conducted at Posyandu Dahlia, Kabasiran Village, Parung Panjang District, Bogor Regency, involving 13 posyandu cadres as the main targets. This program was implemented through socialization, nutrition education, training on planting and processing local foods, and the application of hydroponic technology. The results showed that the stunting prevention program based on three pillars—nutrition education, hydroponic cultivation training, and local food utilization—significantly improved cadre capacity. Nutrition education increased knowledge (p<0.05) in detecting and preventing stunting. NFT-based hydroponic training enhanced cadre skills by 87%, enabling the production of nutritious vegetables for supplementary feeding. Meanwhile, local food processing training encouraged food diversification and community self-reliance. The synergy among these three pillars establishes a sustainable intervention model for reducing stunting prevalence effectively at the community level. In conclusion, the Nutrition Kitchen Program successfully increased the capacity of posyandu cadres in stunting prevention efforts through local food-based interventions. The suggestion for future activities is to conduct activities up to the harvesting process, with the results distributed to toddlers visiting the posyandu.